DORMANCY BREAKING IN RED RICE: TEMPERATURE AND STORAGE PERIOD AND SEED PHYSICAL INTEGRITY ACTIONS - AGOSTINETTO, Dirceu; FLECK, Nilson Gilberto; COSTA, Emerson Luiz Nunes; VIDAL, Ribas Antonio; MEROTTO JÚNIOR, Aldo (Scientia Agraria, 2001)
Occurrence of low temperature during the cold season and physical damage suffered by seeds stored into soil are factors that may affect dormancy breaking in red rice seeds. Two experiments were carried out with the aim to evaluate the effects of storage period and temperature and physical integrity of red rice seeds on the process of dormancy breaking. In the first one, treatments consisted of three seed storage temperatures (-10, 10, and 20º C), two germination temperatures (20 and 30º C), two seed integrity conditions (intact and dehulled), and four germination times after seed harvesting (14, 28, 42, and 56 days). The second experiment tested three integrity conditions of the seeds (intact, dehulled, and bored) and was performed at two periods (8 and 110 days after seed harvesting). The experimental design used in both trials was a completely randomized one, with five replicates. Variable evaluated was seed germination percentage. Results obtained allow to conclude that maintenance of low temperature during seed storage extends post-ripening dormancy, and that dormancy lessens with increasing of seed storage period under temperature of 20º C.